Late Paleogene rifting along the Malay Peninsula thickened crust - Benjamin Sautter, Manuel Pubellier, Pierre Jousselin, Paolo Datt, . (2016)
Sedimentary basins often develop above internal zones of former orogenic belts. We hereafter consider the Malay Peninsula (Western Sunda) as a crustal high separating two regions of stretched continental crust; the Andaman/Malacca basins in the western side and the Thai/Malay basins in the east. Several stages of rifting have been documented thanks to extensive geophysical exploration.